"Cells‐to‐cDNA on Chip": Phenotypic Assessment and Gene Expression Analysis from Live Cells in Nanoliter Volumes Using Droplet Microarrays. Issue 12 (31st March 2022) - Chakraborty, Shraddha; Luchena, Charlotte; Elton, Jonathan J.; Schilling, Marcel P.; Reischl, Markus; Roux, Margaux; Levkin, Pavel A.; Popova, Anna A.
Abstract: In vitro cell‐based experiments are particularly important in fundamental biological research. Microscopy‐based readouts to identify cellular changes in response to various stimuli are a popular choice, but gene expression analysis is essential to delineate the underlying molecular dynamics in cells. However, cell‐based experiments often suffer from interexperimental variation, especially while using different readout methods. Therefore, establishment of platforms that allow for cell screening, along with parallel investigations of morphological features, as well as gene expression levels, is crucial. The droplet microarray (DMA) platform enables cell screening in hundreds of nanoliter droplets. In this study, a "Cells‐to‐cDNA on Chip" method is developed enabling on‐chip mRNA isolation from live cells and conversion to cDNA in individual droplets of 200 nL. This novel method works efficiently to obtain cDNA from different cell numbers, down to single cell per droplet. This is the first established miniaturized on‐chip strategy that enables the entire course of cell screening, phenotypic microscopy‐based assessments along with mRNA isolation and its conversion to cDNA for gene expression analysis by real‐time PCR on an open DMA platform. The principle demonstrated in this study sets a beginning for myriad of possible applications to obtain detailed information about the molecular dynamics in cultured cells. Abstract : Droplet microarray (DMA) platform allows the formation of hundreds of separated miniaturized reservoirs for high throughput cell screenings. In this study, Chakraborty et al. have developed "Cells‐to‐cDNA on Chip" methodology to use DMA as a wall‐free, "sample in ‐ answer out" system for live‐cell screening, microscopy‐based readouts, nucleic acid isolation, and manipulation of the same in micro‐ or nanoliter volumes for quantitative gene expression analysis.